Performance evaluation method of composite porous geopolymer for heavy metal adsorption
Through the combination of composite porous polymer materials and nuclear magnetic resonance technology, the problem of taking into account the adsorption performance and recycling efficiency of existing materials is solved, and efficient adsorption and convenient separation of heavy metals in water bodies is achieved, which is suitable for pollution repair and supports the reuse of materials.
Patent Information
- Application Number
- CN202411930345.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-12-25
AI Technical Summary
The existing polymer porous materials are difficult to balance the adsorption performance of heavy metals and the recovery efficiency, resulting in insufficient adsorption performance or difficulty in recycling heavy metal pollution in water.
The composite porous polymer material is used to obtain the concentration distribution information inside the material through nuclear magnetic resonance technology, and the material preparation process is optimized to improve adsorption performance and recovery efficiency.
It realizes efficient adsorption and convenient separation of heavy metals in water bodies, is suitable for wastewater treatment and groundwater pollution restoration, and the materials can be reused.
Smart Images

Figure CN119715656A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of environmental pollution remediation and treatment, and in particular to a performance evaluation method of a composite porous geopolymer for heavy metal adsorption. Background Art
[0002] With the continuous development of urbanization and industrialization, groundwater bodies are also facing unprecedented pollution threats, among which heavy metal pollution is particularly concerning. Heavy metal ions represented by manganese, chromium, cadmium, etc. have serious effects on water quality, harm human health and damage the ecological environment due to their high toxicity, difficulty in degradation and easy absorption by organisms. Commonly used methods for removing heavy metals from water bodies include chemical precipitation, ion exchange, material adsorption, evaporation concentration, etc. Among them, adsorption is widely used due to its advantages of high efficiency, environmental protection, relatively low cost, high recycling rate and wide applicability. In recent years, geopolymers, as an inorganic aluminosilicate gel material with a three-dimensional mesh molecular sieve structure, have become a new research hotspot in adsorption materials.
[0003] Compared with adsorption materials such as activated carbon, chitosan, and diatomaceous earth, the preparation process of geopolymers is energy-saving and environmentally friendly, the raw materials are widely available, and they have excellent mechanical properties and stable chemical properties. They have shown extremely high adsorption efficiency in the removal of heavy metals such as lead, chromium, and cobalt. In particular, porous geopolymers, the interconnected or closed pore spaces formed inside them make this type of material exhibit characteristics such as low density and high specific surface area, further broadening the application scenarios of geopolymers as adsorption materials. At present, geopolymer porous materials are mainly layered, spherical, and block structures, and are often prepared by direct foaming, solvent volatilization, porous filler addition, and suspension solidification. The internal pore structures formed based on different principles differ in pore size distribution, connectivity characteristics, and other aspects, which directly affect the adsorption performance and application fields of geopolymer porous materials.
[0004] In addition to improving the design ideas and synthesis processes of geopolymer porous materials themselves, the use of advanced heavy metal detection technology to characterize the adsorption process in real time is also an important link in guiding and optimizing material preparation. At present, the main methods for measuring the concentration of heavy metals in water bodies include chromatography, spectroscopy, flow analysis detection, biochemical analysis, etc. Among them, the most commonly used is the combined detection technology of combined spectroscopy and mass spectrometry, including atomic absorption spectroscopy (AAS), inductively coupled plasma atomic emission spectroscopy (ICP-OES), atomic fluorescence spectroscopy (AFS), visible ultraviolet spectrophotometry (UV-Vis) and inductively coupled plasma mass spectrometry (ICP-MS).
[0005] Two major aspects need to be considered when evaluating the ability of different geopolymer materials to remove heavy metals from water bodies: one is the adsorption performance of the material itself. Generally, the larger the specific surface area, the higher the adsorption efficiency; the other is the ease of recovering the material from the water body, thereby achieving pollutant separation and material reuse.
[0006] In terms of adsorption performance, spherical geopolymer porous materials have a larger specific surface area and lower flow resistance than block porous materials due to the presence of surface and internal interconnected pores, and can more efficiently achieve the adsorption and immobilization of heavy metals in water bodies. However, it is difficult to quickly collect and recycle such materials, especially in the remediation of groundwater heavy metal pollution, which is not conducive to the long-term treatment of polluted areas and the reuse of materials. Although block-shaped geopolymer porous materials are conducive to unified disposal, the connectivity and uniformity of the internal pore structure are difficult to control during the preparation process. If the pores formed have a larger pore size, it is conducive to pore penetration so that the polluted water body and the adsorption material are fully in contact, but a certain specific surface area will be lost; if the pores formed have a smaller pore size, it is likely to produce a large number of closed and isolated pore spaces, making it impossible for water to flow through the above-mentioned areas, thereby significantly reducing the adsorption performance. It can be seen that there is an urgent need for a new type of geopolymer porous material that can take into account both adsorption performance and recovery efficiency to meet the application needs of efficient adsorption and separation of heavy metals in water bodies.
[0007] For monitoring adsorption characteristics, the combined detection technology based on spectroscopy and mass spectrometry can only measure the heavy metal concentration of the whole solution or the outflow end, but cannot obtain the concentration distribution information inside the geopolymer material. Therefore, the detection data is difficult to use to analyze the dynamic characteristics and spatial differences of the adsorption process. However, this information is often an important parameter for exploring the effect of the pore structure of geopolymer porous materials on the adsorption behavior of heavy metals. It can not only comprehensively evaluate the adsorption performance of different materials, but also be used to improve the synthesis and preparation process of geopolymer porous materials, so as to obtain porous geopolymers with better performance for the adsorption of heavy metals in water bodies. Summary of the invention
[0008] The object of the present invention is to at least partially overcome the defects of the prior art and provide a method for evaluating the performance of a composite porous geopolymer for heavy metal adsorption.
[0009] The present invention also aims to provide a performance evaluation method for a composite porous geopolymer for heavy metal adsorption, which can obtain the concentration distribution information inside the geopolymer material.
[0010] The present invention also aims to provide a performance evaluation method for a composite porous geopolymer for heavy metal adsorption, which can characterize the adsorption process and guide and optimize material preparation.
[0011] To achieve the above purpose or one of the purposes, the technical solution of the present invention is as follows:
[0012] A performance evaluation method for a composite porous geopolymer for heavy metal adsorption, the performance evaluation method comprising:
[0013] Step 1: Prepare heavy metal solutions of different concentrations;
[0014] Step 2: Establish a calibration line between the heavy metal solution concentration and the nuclear magnetic resonance signal;
[0015] Step 3: Conduct adsorption experiments on multiple batches of composite porous geopolymer materials based on nuclear magnetic resonance technology;
[0016] Step 4: Monitor and evaluate the adsorption performance of the composite porous geopolymer.
[0017] According to a preferred embodiment of the present invention, step 1 comprises:
[0018] Prepare 500 ml of a heavy metal solution with a concentration of 1000 ppm in a flask as a standard solution;
[0019] A certain amount of solution was gradually taken out with a pipette into a glass bottle with a volume of 10 ml, and heavy metal solutions of different concentrations were prepared by adding different volumes of ultrapure water.
[0020] According to a preferred embodiment of the present invention, step 2 comprises:
[0021] Use the nuclear magnetic resonance pulse sequence to measure heavy metal standard solutions of different concentrations to obtain T2 values;
[0022] Establish the relationship between heavy metal ion concentration and NMR signal [1 / T 2,i -1 / T 2,0 ], that is, to determine the marking line, where T 2,i is the measured transverse relaxation time, ms; T 2,0 is the transverse relaxation time of ultrapure water, ms.
[0023] According to a preferred embodiment of the present invention, step 2 comprises:
[0024] Turn on the radio frequency switch of the low-field nuclear magnetic resonance instrument, use the oil sample to adjust the main frequency and sampling frequency, adjust the initial parameters, and in the SFG-MSCPMG pulse sequence, set the repeated sampling waiting time to 6000ms, the echo time to 0.2ms, the number of echoes to 8000, the number of layers to 1, and the number of accumulations to 2;
[0025] Use this sequence to test heavy metal solution samples of different concentrations to obtain the corresponding T2 values, where the correlation between the concentration of the heavy metal solution and T2 is shown in the following formula:
[0026]
[0027] Where C is the concentration of heavy metal solution, mM; R is the transverse relaxation rate, mM·s -1 ; T 2,i is the measured transverse relaxation time, ms; T 2,0 is the transverse relaxation time of ultrapure water, ms.
[0028] According to a preferred embodiment of the present invention, the transverse relaxation time T2 is measured using a SFG-MSCPMG pulse sequence based on a constant gradient encoding technique.
[0029] According to a preferred embodiment of the present invention, each time a predetermined number of samples are measured, an additional sample of ultrapure water is measured as a calibration.
[0030] According to a preferred embodiment of the present invention, step 3 comprises: placing different forms of geopolymer porous samples in a nuclear magnetic resonance holder in turn, first saturating them with ultrapure water, and then injecting heavy metal ion solutions of the same concentration at the same flow rate, and monitoring the concentration distribution characteristics and dynamic changes of the heavy metal solution inside the sample in real time based on nuclear magnetic resonance technology.
[0031] According to a preferred embodiment of the present invention, step 3 further includes: collecting the effluent at the outlet end of the holder, and performing static measurement of the heavy metal concentration every time 2 ml is collected; combining with the established heavy metal ion concentration line, converting the nuclear magnetic resonance measurement data into the concentration of heavy metal ions in the effluent at different times, thereby quantifying and evaluating the adsorption behavior of different forms of geopolymer porous samples.
[0032] According to a preferred embodiment of the present invention, computer tomography and scanning electron microscopy are used to characterize the structure of geopolymer porous samples, analyze the porosity, pore size distribution, and connectivity, and establish a correlation between pore structure and adsorption performance.
[0033] According to a preferred embodiment of the present invention, in step 3, porous geopolymer samples of different forms are placed in a nuclear magnetic resonance holder in sequence to conduct displacement adsorption experiments to characterize the adsorption properties of different materials, including:
[0034] Use a pipette to take out 80 ml of the 1000 ppm standard solution, add 320 ml of ultrapure water, and prepare a total volume of 400 ml of 200 ppm standard solution for adsorption experiments;
[0035] Before each displacement adsorption experiment, ultrapure water was injected at a flow rate of 0.1 ml / min for 30 min to make the sample to be tested fully saturated;
[0036] Subsequently, a standard solution with a concentration of 200 ppm was continuously injected at a flow rate of 0.1 ml / min for 40 minutes, and then ultrapure water was injected at a flow rate of 0.1 ml / min. The total experimental time was 80 minutes; or a standard solution with a concentration of 200 ppm was continuously injected at a flow rate of 0.2 ml / min for 20 minutes, and then ultrapure water was injected at a flow rate of 0.1 ml / min. The total experimental time was 60 minutes.
[0037] According to a preferred embodiment of the present invention, in step 3, a static adsorption experiment is performed to test the adsorption capacity of the granular porous material of the composite porous geopolymer, comprising:
[0038] Dispense the prepared 200 ppm standard solution into two identical glass containers respectively;
[0039] Then weigh 1g of each of the ground granular porous materials with mesh sizes of 25-30 and 12-14 and put them into a glass container, making sure that the liquid level can submerge the sample and is more than 2 cm higher;
[0040] The timing started immediately after the sample was placed in the container. Every 5 minutes, 2 ml of solution sample was taken out from the container with a pipette and injected into the chromatographic bottle for nuclear magnetic resonance measurement to monitor the adsorption behavior. The total experiment time was 60 minutes.
[0041] The performance evaluation method of the composite porous geopolymer for heavy metal adsorption of the present invention can obtain the concentration distribution information inside the geopolymer material, and the detection data can be used to analyze the dynamic characteristics and spatial differences of the adsorption process, which is important for exploring the influence of the pore structure of the porous geopolymer material on the heavy metal adsorption behavior. It can not only comprehensively evaluate the adsorption performance of different materials, but also be used to improve the synthesis and preparation process of the porous geopolymer material, so as to obtain a porous geopolymer with better performance for the adsorption of heavy metals in water bodies. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] Figure 1 The production process and physical diagram of the composite geopolymer porous adsorption material according to an embodiment of the present invention;
[0043] Figure 2 The correlation between the concentration of Mn(II) solution and the NMR signal is shown;
[0044] Figure 3 Pore structure characterization of geopolymer porous materials is shown;
[0045] Figure 4 The heavy metal concentration distribution information inside the geopolymer porous material is shown;
[0046] Figure 5A comparison of the adsorption properties of granular porous filling materials with different mesh sizes is shown. DETAILED DESCRIPTION
[0047] Exemplary embodiments of the present invention are described in detail below in conjunction with the accompanying drawings, wherein the same or similar reference numerals represent the same or similar elements. In addition, in the detailed description below, for ease of explanation, many specific details are set forth to provide a comprehensive understanding of the disclosed embodiments. However, it is apparent that one or more embodiments may also be implemented without these specific details. In other cases, known structures and devices are embodied in a schematic manner to simplify the accompanying drawings.
[0048] The present invention belongs to the technical field of environmental pollution remediation and treatment, and specifically involves the design and synthesis of composite geopolymer porous materials, and the comprehensive evaluation of their heavy metal adsorption performance based on nuclear magnetic resonance technology, thereby proposing an application technology that can achieve efficient adsorption and convenient separation of heavy metals in water bodies, which is suitable for wastewater treatment, groundwater pollution remediation and other fields.
[0049] The present invention aims to establish an application technology of integrated heavy metal adsorption-separation in water bodies that is efficient, economical and environmentally friendly. Aiming at the problem of heavy metal removal in water bodies, a composite geopolymer porous material is designed and synthesized, which not only has the advantages of geopolymer as an adsorption material itself being green, environmentally friendly and low-cost, but also achieves the dual goals of efficient adsorption and unified recovery of heavy metals through innovative preparation and integration processes of porous materials.
[0050] Geopolymers are inorganic polymers that undergo depolymerization and polycondensation of the silicon-oxygen bonds and aluminum-oxygen bonds of aluminosilicates in natural minerals or solid wastes (metakaolin, kaolin, and fly ash, etc.) under the conditions of alkali or acid activators, and then gel solidification to produce a three-dimensional network structure. This material is mainly composed of silicon tetrahedrons [Si(OH)4] and aluminum tetrahedrons [Al(OH)4 -] structural units and connected by shared oxygen atoms. Due to its zeolite-like structure, it shows broad application prospects in the adsorption / stabilization of toxic heavy metal ions and other polluting impurities. The porous geopolymer is formed with a through or closed pore space inside by adding a foaming agent, a filler, etc. during the above-mentioned preparation process. These pores and the geopolymer skeleton form a new spatial structure, which further increases the specific surface area of the material, thereby improving the adsorption performance. On the basis of systematic experimental comparative studies, the present invention establishes an optimized geopolymer porous material preparation scheme and process, synthesizes a cylindrical porous material with internally connected pore space, and then transforms its internal structure, and fills and encapsulates a spherical porous material, which greatly increases the total specific surface area of the adsorption material. Thus, a composite geopolymer porous material is proposed, which can achieve efficient adsorption and unified separation of heavy metals in water bodies. With the idea of preparing this composite geopolymer material for pollution remediation, different nuclear magnetic resonance test sequences have been developed for accurate, rapid and non-destructive measurement of heavy metal concentrations, in order to obtain the spatiotemporal information of the heavy metal concentration distribution inside the geopolymer, which can be used to guide and improve the preparation parameters and processes of the composite material, thereby determining the material synthesis scheme with the best adsorption performance.
[0051] The specific technical method of the present invention is as follows:
[0052] (1) Preparation of geopolymer porous materials with through pores
[0053] The preparation process of geopolymer porous materials includes mixing and stirring the aluminosilicate raw materials with liquid activators, adding foaming agents and foam stabilizers to form a uniform slurry, injecting and compacting the mixture into a mold, and then curing and curing under certain conditions. In addition to the selection of synthetic materials, the key parameters in the preparation scheme also include the modulus of the activator (i.e., the molar ratio between SiO2 and Na2O), the liquid-to-solid ratio (i.e., the mass ratio between water and solid solution in the uniform slurry), the molar ratio between the foaming agent and the foam stabilizer, and the temperature of the curing process. The relevant parameters jointly control the adsorption performance and mechanical properties of the prepared geopolymer porous materials. Based on the comparative optimization of systematic experimental tests, the present invention selects mixed NaOH and Na2SiO3 as the composite alkaline activator solution, and the activator modulus is 1.4; a mixture of fly ash and kaolin with a mass ratio of 1:1 is used as the raw material, and the total liquid-solid ratio is 1.15; 3% hydrogen peroxide is used as the foaming agent, and sodium dodecyl sulfate is used as the foam stabilizer, and the mixing ratio of the two is 1:1; the mold injected with the slurry is first placed in a microwave oven, set the 300W gear microwave for 150 seconds to further promote the foaming effect and rapid curing, and then take it out and place it in an oven at 40°C for thermal curing for 18 hours, and finally demold and seal it for storage, and maintain it at room temperature for 28 days. The mold uses a cylindrical container with a diameter of 10 mm and a length of 60 mm, and polishes both ends to obtain a cylindrical geopolymer porous material with a length of 50 mm.
[0054] (2) Synthetic composite geopolymer porous adsorption material
[0055] The cylindrical geopolymer porous material is cut into 50 mm lengths, and a hollow drill bit with a diameter of 5 mm is used to remove the middle part of the cylindrical porous material to obtain a 50 mm long circular porous material. The removed part is first cut at both ends, leaving 5 mm on each side, and the rest is ground to 25-30 mesh for filling. Figure 1 As shown, the ground geopolymer porous material is loaded inside the annular geopolymer material, and the two ends are assembled and sealed with cut 5 mm thin sheets (cylindrical blocks), and finally a composite geopolymer porous adsorption material is obtained. Compared with the porous material of single columnar or spherical particles, this material has the advantages of both structural types of materials. It not only has a large specific surface area, but also can more fully allow the water containing heavy metals to contact with the adsorption material, and adsorb heavy metals in the process of flowing through the annular porous material and entering the porous material filled with internal particles, thereby purifying the water. In addition, the composite material can be easily and uniformly recycled for subsequent material replacement, regeneration and reuse.
[0056] (3) Establish heavy metal concentration benchmarks based on nuclear magnetic resonance technology
[0057] Low-field Nuclear Magnetic Resonance (NMR) can detect hydrogen protons in a solution non-destructively, accurately, and quickly. If the solution contains paramagnetic heavy metal ions, the attenuation of the NMR signal will be accelerated, thereby establishing a correlation between the concentration of heavy metal ions and the NMR signal. Among them, the response of the NMR signal can be characterized by measuring the transverse relaxation time T2, which characterizes the time it takes for the atomic nucleus with a dipole magnetic moment to recover from the excited state to the equilibrium state through a spin-spin method after the application of the above-mentioned radio frequency wave is stopped. First, use ultrapure water to configure the heavy metal ions into standard liquids of different concentrations and put them into glass bottles for use; then use a NMR pulse sequence to measure the heavy metal standard solutions of different concentrations to obtain the T2 value; finally, establish the relationship between the heavy metal ion concentration in the solution and the NMR signal [1 / T 2,i -1 / T 2,0 ], the calibration line is determined for accurate and rapid measurement of heavy metal ion concentration in subsequent adsorption experiments.
[0058] In addition to the effect of heavy metal concentration on T2 value, the pore structure of geopolymer porous materials will also affect the NMR signal, as described in the following equation:
[0059]
[0060] Where ρ0 is the surface relaxation rate, S and V are the specific surface area and volume of the porous medium, respectively. Although the pore structure and heavy metal concentration jointly affect the NMR data T2, the two effects are independent of each other. For a specific heavy metal ion, its concentration and NMR signal [1 / T 2,i -1 / T 2,0 ] does not change due to the pore structure. Therefore, in a geopolymer porous material with a fixed structure, the change in the nuclear magnetic resonance signal during the adsorption process depends on the change in the heavy metal concentration. According to the above principle, the acquired nuclear magnetic resonance T2 data can be converted into the concentration distribution information and dynamic characteristics inside the porous material, realizing non-destructive real-time monitoring of the heavy metal adsorption behavior inside the geopolymer material.
[0061] For the measurement of nuclear magnetic resonance T2 data, the SFG-MSCPMG pulse sequence based on constant gradient coding technology is used. This sequence can not only measure the heavy metal concentration in the whole sample like the traditional CPMG sequence, but also generate different positioning information under the action of the gradient magnetic field generated by the gradient coil. By using mathematical conversion decoding, the nuclear magnetic signal can be allocated to different spatial positions, so that the distribution characteristics of heavy metal ions in the geopolymer can be obtained. The so-called constant gradient coding technology is a technology that applies selective radio frequency pulses and uses a radio frequency pulse with a limited bandwidth to perform resonance excitation only on protons with a resonance frequency in the frequency band. After applying a gradient in a certain direction, the layer selection excitation pulse can achieve selective excitation, while the hydrogen protons outside the selection layer do not meet the resonance conditions and cannot be excited, so no nuclear magnetic signal is generated. By setting the number of layers, the overall nuclear magnetic signal (setting one layer) and the concentration data at different positions (setting ten layers) can be obtained.
[0062] (4) Evaluation of the adsorption performance of composite geopolymer porous materials
[0063] Based on the established method for monitoring the dynamic behavior of heavy metal ion concentration, adsorption experiments were carried out on composite and unmodified cylindrical geopolymer porous materials to quantitatively compare the adsorption performance of the two. The two geopolymer porous materials were placed in the holder of the nuclear magnetic resonance equipment in turn, first saturated with ultrapure water, and then injected with heavy metal ion solutions of the same concentration at the same flow rate. The concentration distribution characteristics and dynamic changes of the heavy metal solution inside the sample were monitored in real time based on the nuclear magnetic resonance technology. At the same time, the effluent was collected at the outlet of the holder, and the static measurement of heavy metal concentration was performed every 2 ml collected. Combined with the established heavy metal ion concentration line, the nuclear magnetic resonance measurement data was converted into the concentration of heavy metal ions in the effluent at different times, so as to quantify and evaluate the overall adsorption behavior of different materials. In addition, computed tomography (CT) and scanning electron microscope (SEM) were used to characterize the structure of the prepared composite geopolymer porous material, and its pore structure parameters related to adsorption behavior, such as porosity, pore size distribution, and connectivity, were analyzed to establish a correlation between pore structure and adsorption performance.
[0064] The following describes the specific experimental steps by taking the adsorption of heavy metal manganese Mn(II) by composite geopolymer porous materials as an example:
[0065] S1: Raw materials and equipment for preparing composite geopolymer materials
[0066] Add granular sodium hydroxide to sodium water glass (alkali metal silicate formed by combining alkali metal oxides and silicon dioxide) with an initial modulus of 2.3 to prepare an alkaline activator, and adjust its modulus to 1.4. Stir thoroughly to dissolve the added sodium hydroxide completely, and let it stand at room temperature for more than 24 hours. When the activator liquid turns from the turbid state at the initial mixing to a transparent state, it can be used for the subsequent preparation of the polymer. Use 3% hydrogen peroxide as a foaming agent and sodium dodecyl sulfate as a foam stabilizer. Mix the two in a molar ratio of 1:1, stir evenly and set aside.
[0067] A certain mass of fly ash and metakaolin was placed in an oven and dried at 80°C for 12 hours, and then 50g of fly ash and metakaolin raw materials were weighed on a balance and mixed for later use. The particle sizes of fly ash and metakaolin raw materials used in this study were 5μm and 3.75μm, respectively. The main chemical components and contents measured by X-ray fluorescence spectrometer are shown in Tables 1 and 2. Since the chemical composition of raw materials obtained from different sources is different, the optimal raw material ratio varies.
[0068] Table 1 Main chemical composition and content of fly ash
[0069]
[0070] Table 2 Main chemical components and contents of metakaolin
[0071]
[0072] The low-field nuclear magnetic resonance imaging analyzer used in the test analysis is the Meso MR23-060H from Suzhou Newmai Analytical Instruments Co., Ltd., the X-ray fluorescence spectrometer is the LH-XRFⅡ from Tianjin Luhai Petroleum Equipment System Engineering Co., Ltd., and the computer tomography equipment is the Xradia 510Versa from Carl Zeiss of Germany. The mixing process of different materials in the preparation of geopolymers uses a cement slurry mixer from Shaoxing Shangyu Binxin Instrument Factory, model NJ-160B.
[0073] S2: Preparation and curing of composite geopolymer porous materials
[0074] First, add the mixture of fly ash and metakaolin as raw materials to the composite alkaline activator solution with a modulus of 1.4, mix thoroughly and pour into the cement slurry mixer, put the pot on the pot base of the mixer, raise it to the stirring position, start the mixer, stir at a low speed, mix evenly, and this process lasts for 10 minutes. After stopping, add the prepared foaming agent and foam stabilizer mixture, as well as ultrapure water to make the liquid-solid ratio of 1.15, mix thoroughly and then turn on the cement slurry mixer to stir at a low speed for 5 minutes. Then scrape the slurry on the blades and the pot wall into the middle of the pot, pour the stirred slurry into four identical cylindrical special molds with a diameter of 10 mm and a length of 60 mm, and shake, compact and seal. The curing process adopts a dual mode of microwave heating and oven heating. First, the mold injected with the slurry is placed in a microwave oven and microwaved at 300W for 150 seconds. Then it is taken out and placed in an oven at 40°C for heat curing for 18 hours. After taking it out and demolding it, it is sealed on all sides with a sealing mold and cured at room temperature for 28 days.
[0075] Thus, four cylindrical geopolymer porous samples of the same size were prepared, two of which were cut into 50 mm lengths and reserved for later use, and the other two were used to prepare composite geopolymer porous materials. First, the middle of the cylindrical porous material was taken out with a hollow drill bit with a diameter of 5 mm, and the two ends were cut, and a 5 mm thick slice was retained for subsequent composite sample packaging, and the rest was ground to 25-30 mesh for filling inside the ring. After the ground porous material was filled into the cylindrical material, two 5 mm slices were covered at the two ends, and the four sides were sealed with the ring sample with epoxy resin glue, thereby obtaining two composite geopolymer porous materials.
[0076] S3: Prepare heavy metal Mn(II) solutions of different concentrations
[0077] The Mn(II) standard solution was diluted with ultrapure water. First, 500 ml of a 1000 ppm Mn(II) solution was prepared in a flask. Then, different amounts of the solution were gradually taken out with a pipette into a 10 ml glass bottle for dilution. The Mn(II) solutions of different concentrations prepared by adding different volumes of ultrapure water were used for line determination. Finally, 20 Mn(II) solution samples with concentrations of 0.025, 0.05, 0.5, 0.8, 1, 2, 5, 8, 10, 30, 50, 60, 80, 100, 200, 400, 600, 800, 900, and 1000 ppm were obtained.
[0078] S4: Establishing a line between Mn(II) solution concentration and NMR signal
[0079] Turn on the RF switch of the low-field NMR instrument and use the oil sample to adjust the main frequency and sampling frequency. Adjust the initial parameters. In the SFG-MSCPMG pulse sequence, the repeated sampling waiting time (TW) is set to 6000ms, the echo time (TE) is 0.2ms, the number of echoes is 8000, the number of layers is 1, and the number of accumulations is 2. Use this sequence to test 20 Mn(II) solution samples with different concentrations and obtain the corresponding T2 values. Among them, the correlation between the concentration of Mn(II) and T2 is shown in the formula:
[0080]
[0081] Where C is the concentration of Mn(II) solution, mM; R is the transverse relaxation rate, mM·s -1 ; T 2,i is the measured transverse relaxation time, ms; T 2,0 is the transverse relaxation time of ultrapure water, ms. During the test, every 10 samples were tested, an ultrapure water sample was added for calibration (the T2 value of ultrapure water is ≈ 2800ms). The final calibration line is as follows: Figure 2 As shown, according to Formula 2, the concentration of Mn(II) can be related to [1 / T 2,i -1 / T 2,0 ] to obtain the nuclear magnetic relaxation rate R of Mn(II) ion as 9.45 mM·s -1 , the goodness of fit is 0.9998. Since the effects of pore structure and heavy metal concentration on NMR signals are independent of each other, the NMR relaxation rate of Mn(II) ions will not change inside the geopolymer porous material with fixed structure, and the measured calibration line is still applicable.
[0082] S5: Conduct adsorption experiments on multiple batches of composite geopolymer materials
[0083] The two unmodified cylindrical geopolymer porous samples prepared in S2 and the two modified composite geopolymer porous samples were placed in the NMR holder for displacement experiments to characterize the adsorption properties of different materials. First, 80 ml of the 1000ppm Mn(II) standard solution prepared in step S3 was taken out using a pipette, and then 320 ml of ultrapure water was added to prepare a total volume of 400 ml of 200ppm Mn(II) standard solution for adsorption experiments. Before each displacement experiment, ultrapure water was injected at a flow rate of 0.1ml / min for 30min to make the sample to be tested fully saturated. Subsequently, Mn(II) with a concentration of 200ppm was continuously injected at a flow rate of 0.1ml / min for 40 minutes, and then ultrapure water was injected at a flow rate of 0.1ml / min. The total experimental time was 80min. Alternatively, Mn(II) with a concentration of 200 ppm was continuously injected at a flow rate of 0.2 ml / min for 20 minutes, and then ultrapure water was injected at a flow rate of 0.1 ml / min. The total experimental time was 60 minutes to ensure that the heavy metal expulsion rate was consistent with that of another batch of experiments, focusing on comparing the effect of the injection flow rate of the heavy metal solution on the adsorption behavior of the porous material.
[0084] In addition to the displacement adsorption experiment, a static adsorption experiment was also conducted to test the adsorption capacity of the granular porous material filled inside the composite material. First, the prepared 200ppm Mn(II) standard solution was divided into two identical glass containers, and then 1g of each of the ground granular porous materials with mesh sizes of 25-30 and 12-14 were weighed and placed in the glass containers to ensure that the liquid level could submerge the sample and be more than 2 cm higher. The adsorption experiment started after the sample was placed, and the timing started immediately. Every 5 minutes, 2ml of solution sample was taken out from the container with a pipette and injected into the chromatographic bottle for nuclear magnetic resonance measurement to monitor the adsorption behavior. The total duration of the experiment was 60 minutes.
[0085] S6: Monitoring and evaluating the adsorption performance of composite geopolymer materials
[0086] The displacement adsorption experiment uses the nuclear magnetic resonance SFG-MSCPMG pulse sequence for real-time testing to obtain the distribution characteristics of heavy metal ions inside the porous material. First, turn on the radio frequency unit of the low-field nuclear magnetic resonance instrument and adjust the parameters. The adjustment steps are the same as S4. Use the SFG-MSCPMG pulse sequence (10 layers) and the other setting parameters as described in S4. Test once every 10 minutes. Use the Mn (II) solution concentration line established in S4 to calculate the solution concentration of different experimental groups and at different times, so as to characterize the dynamic adsorption process.
[0087] The static adsorption experiment uses the nuclear magnetic resonance SFG-MSCPMG pulse sequence for real-time testing, but the layer selection is set to 1 layer to test the overall concentration signal of the heavy metal ion solution. The other setting parameters are as described in S4. Turn on the radio frequency unit of the low-field nuclear magnetic resonance instrument, adjust the parameters, and the adjustment steps are the same as S4. The concentration of the Mn (II) solution samples collected at the outflow end at different time points is tested. The chromatographic bottle containing the sample is placed in the test coil of the low-field nuclear magnetic resonance instrument, and the concentration is measured using the SFG-MSCPMG pulse sequence.
[0088] In addition, the pore structure of the spare sample of cylindrical geopolymer porous material was characterized. From the image results, it can be seen that the pores of the geopolymer porous material are densely developed, with a total porosity of 56.2%, of which the larger pore diameter is about 1.34mm, and the smaller pore diameter is concentrated at 0.635mm. The overall pore connectivity is good, and the connected porosity is 50.2%. The particle size of the granular porous material inside the composite geopolymer porous material is 0.6-0.71mm (25-30 mesh), which can be well filled in the middle of the prepared annular porous material without leakage.
[0089] In the displacement adsorption test, different heavy metal solution injection flow rates were set to compare the adsorption performance differences between cylindrical and composite geopolymer porous materials. The test method based on the nuclear magnetic resonance SFG-MSCPMG pulse sequence can obtain the heavy metal concentration distribution information inside the geopolymer porous material in real time and non-destructively. The relevant results are as follows Figure 4 shown. Figure 4 (a)-(b) are experiments in which heavy metal solution was injected at a flow rate of 0.1 ml / min. Figure 4 (a) is the concentration distribution inside the porous material at 20 minutes of experiment. Figure 4 (b) is the heavy metal concentration at the outflow end at different times. Compared with the unmodified cylindrical porous geopolymer, the composite geopolymer material can quickly adsorb heavy metal ions in the system near the injection end, and no heavy metal ions are detected at the outflow end (e.g. Figure 4 (b)). Although the unmodified cylindrical porous geopolymer can remove heavy metals in the system at the beginning of the experiment, as more heavy metal ions are injected, a small amount of heavy metal ions can still be detected flowing out of the solution at the outflow end.
[0090] Figure 4 (c)-(d) are experiments in which heavy metal solution was injected at a flow rate of 0.2 ml / min. Figure 4 (c) is the concentration distribution inside the porous material at 10 minutes of experiment. Figure 4(d) is the heavy metal concentration at different times at the outflow end. Under faster injection conditions, the difference in adsorption performance of the two materials is more obvious. Compared with the slow flow rate scenario, the composite porous material can always completely adsorb the injected heavy metal ions, but it requires relatively more adsorption material, while the adsorption rate of the cylindrical porous polymer is difficult to match the injection rate of heavy metal ions, so that a certain amount of heavy metal outflow can be detected at the outflow end.
[0091] The static adsorption experiment compared the adsorption rate and adsorption capacity of granular porous fillers with different mesh sizes. Figure 5 As shown, porous materials with larger mesh sizes (25-30), i.e., finer particles, can more quickly and fully adsorb heavy metal ions in water because of their larger specific surface area. After 20 minutes of adsorption experiment, the adsorption amount of porous materials with smaller particles was 71.1% higher than that of materials with larger particles, and at the end of the experiment, the total adsorption amount of materials with smaller particles was 46.4% higher than that of materials with larger particles. The above results fully demonstrate that the use of porous materials with smaller particles as filling materials inside composite porous geopolymers can greatly improve the overall adsorption performance of the materials. In addition, taking out the materials after the experiment can achieve the rapid separation of heavy metal pollutants from water.
[0092] Compared with the prior art, the present invention has the following beneficial effects:
[0093] (1) The designed composite geopolymer porous material can significantly increase the specific surface area of the block porous material, thereby greatly increasing the adsorption rate of heavy metals in water by the geopolymer.
[0094] (2) The designed composite geopolymer porous material helps the fluid flow into the interior of the material, allowing heavy metal ions to fully contact the internal granular porous material, significantly improving the adsorption capacity of the same mass of material.
[0095] (3) The designed composite geopolymer porous material can achieve efficient removal of heavy metal ions even when the polluted water flows through it at a relatively fast speed.
[0096] (4) The designed composite geopolymer porous material can achieve centralized and convenient separation from the water body while ensuring the adsorption performance. It is particularly suitable for groundwater pollution remediation and treatment, which can facilitate the long-term and effective operation of the remediation device and realize the recovery, regeneration and reuse of the adsorption material.
[0097] The performance evaluation method of the composite porous geopolymer for heavy metal adsorption of the present invention can obtain the concentration distribution information inside the geopolymer material, and the detection data can be used to analyze the dynamic characteristics and spatial differences of the adsorption process, which is important for exploring the influence of the pore structure of the porous geopolymer material on the heavy metal adsorption behavior. It can not only comprehensively evaluate the adsorption performance of different materials, but also be used to improve the synthesis and preparation process of the porous geopolymer material, so as to obtain a porous geopolymer with better performance for the adsorption of heavy metals in water bodies.
[0098] Although the embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that changes may be made to these embodiments without departing from the principles and spirit of the present invention. The scope of application of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for evaluating the performance of a composite porous geopolymer for heavy metal adsorption, characterized in that: The performance evaluation method comprises: Step 1: Prepare heavy metal solutions of different concentrations; Step 2: Establish a calibration line between the heavy metal solution concentration and the nuclear magnetic resonance signal; Step 3: Conduct adsorption experiments on multiple batches of composite porous geopolymer materials based on nuclear magnetic resonance technology; Step 4: Monitor and evaluate the adsorption performance of the composite porous geopolymer.
2. The performance evaluation method of the composite porous geopolymer for heavy metal adsorption according to claim 1, characterized in that: The step 1 comprises: Prepare 500 ml of a heavy metal solution with a concentration of 1000 ppm in a flask as a standard solution; A certain amount of solution was gradually taken out with a pipette into a glass bottle with a volume of 10 ml, and heavy metal solutions of different concentrations were prepared by adding different volumes of ultrapure water.
3. The performance evaluation method of the composite porous geopolymer for heavy metal adsorption according to claim 2, characterized in that: The step 2 comprises: Use the nuclear magnetic resonance pulse sequence to measure heavy metal standard solutions of different concentrations to obtain T2 values; Establish the relationship between heavy metal ion concentration and NMR signal [1 / T 2,i -1 / T 2,0 ], that is, to determine the marking line, where T 2,i is the measured transverse relaxation time, ms; T 2,0 is the transverse relaxation time of ultrapure water, ms.
4. The performance evaluation method of the composite porous geopolymer for heavy metal adsorption according to claim 2, characterized in that: The step 2 comprises: Turn on the radio frequency switch of the low-field nuclear magnetic resonance instrument, use the oil sample to adjust the main frequency and sampling frequency, adjust the initial parameters, and in the SFG-MSCPMG pulse sequence, set the repeated sampling waiting time to 6000ms, the echo time to 0.2ms, the number of echoes to 8000, the number of layers to 1, and the number of accumulations to 2; Use this sequence to test heavy metal solution samples of different concentrations to obtain the corresponding T2 values, where the correlation between the concentration of the heavy metal solution and T2 is shown in the following formula: Where C is the concentration of heavy metal solution, mM; R is the transverse relaxation rate, mM·s -1 ; T 2,i is the measured transverse relaxation time, ms; T 2,0 is the transverse relaxation time of ultrapure water, ms.
5. The performance evaluation method of the composite porous geopolymer for heavy metal adsorption according to claim 3 or 4, characterized in that: The transverse relaxation time T2 was measured using the SFG-MSCPMG pulse sequence based on the constant gradient encoding technique.
6. The performance evaluation method of the composite porous geopolymer for heavy metal adsorption according to claim 5, characterized in that: The step 3 comprises: placing porous geopolymer samples of different forms in a nuclear magnetic resonance holder in turn, first saturating them with ultrapure water, then injecting heavy metal ion solutions of the same concentration at the same flow rate, and monitoring the concentration distribution characteristics and dynamic changes of the heavy metal solution inside the sample in real time based on nuclear magnetic resonance technology.
7. The method for evaluating the performance of a composite porous geopolymer for heavy metal adsorption according to claim 6, characterized in that: The step 3 also includes: collecting the effluent at the outlet of the holder, and performing static measurement of the heavy metal concentration every time 2 ml is collected; combining the established heavy metal ion concentration line, converting the nuclear magnetic resonance measurement data into the concentration of heavy metal ions in the effluent at different times, thereby quantifying and evaluating the adsorption behavior of different forms of geopolymer porous samples.
8. The performance evaluation method of the composite porous geopolymer for heavy metal adsorption according to claim 7, characterized in that: Computed tomography and scanning electron microscopy were used to characterize the structure of porous geopolymer samples, analyze the porosity, pore size distribution, and connectivity, and establish the correlation between pore structure and adsorption performance.
9. The method for evaluating the performance of a composite porous geopolymer for heavy metal adsorption according to claim 8, characterized in that: In step 3, different forms of geopolymer porous samples are placed in the NMR holder in succession to conduct displacement adsorption experiments to characterize the adsorption properties of different materials, including: Use a pipette to take out 80 ml of the 1000 ppm standard solution, add 320 ml of ultrapure water, and prepare a total volume of 400 ml of 200 ppm standard solution for adsorption experiments; Before each displacement adsorption experiment, ultrapure water was injected at a flow rate of 0.1 ml / min for 30 min to make the sample to be tested fully saturated; Subsequently, a standard solution with a concentration of 200 ppm was continuously injected at a flow rate of 0.1 ml / min for 40 minutes, and then ultrapure water was injected at a flow rate of 0.1 ml / min. The total experimental time was 80 minutes; or a standard solution with a concentration of 200 ppm was continuously injected at a flow rate of 0.2 ml / min for 20 minutes, and then ultrapure water was injected at a flow rate of 0.1 ml / min. The total experimental time was 60 minutes.
10. The performance evaluation method of the composite porous geopolymer for heavy metal adsorption according to claim 8, characterized in that: In step 3, a static adsorption experiment is performed to test the adsorption capacity of the granular porous material of the composite porous geopolymer, including: Dispense the prepared 200 ppm standard solution into two identical glass containers respectively; Then weigh 1g of each of the granular porous materials with mesh sizes of 25-30 and 12-14 after grinding and put them into a glass container, making sure that the liquid level can submerge the sample and is more than 2 cm higher; The timing started immediately after the sample was placed in the container. Every 5 minutes, 2 ml of solution sample was taken out from the container with a pipette and injected into the chromatographic bottle for nuclear magnetic resonance measurement to monitor the adsorption behavior. The total experiment time was 60 minutes.
Citation Information
Patent Citations
Geopolymer, preparation method of same and application of same in heavy metal ion adsorption
CN107999022A
Method for preparing heavy metal ion adsorbent by using fly ash aluminum extraction slag
CN113289572A
Cyclodextrin-based nano-porous composite adsorption material and preparation method thereof
CN114849660A
Method for detecting heavy metal adsorption performance of micro-plastic by using low-field NMR relaxation method
CN116106355A
Method for removing heavy metals from wastewater
US20190284063A1